Revitalization of Mapag Panganten: Preserving West Java Culture In The Age of Modernization - Komalasari, Dewi; Susanto, Denddy Rayhan Garland; Nurholis, Egi (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
This study aims to describe the implementation of Mapag Panganten in the modern era, analyze the factors causing its decline, and formulate appropriate revitalization strategies to ensure that this tradition remains sustainable and relevant. This study uses a qualitative approach with ethnographic methods through observation and in-depth interviews with traditional leaders. The results show that the Mapag Panganten tradition has undergone a transformation in form as an adaptation to modern lifestyles. The challenges faced include low knowledge regeneration, minimal policies, and the dominance of popular culture. Revitalization strategies that can be used include strengthening the role of indigenous communities and art studios, local cultural education in schools, holding cultural festivals, and utilizing digital media as a means of documentation and promotion. This research is expected to be a concrete effort in preserving the sustainability of Mapag Panganten as a Sundanese cultural heritage amid the tide of modernization.